Dermatopathia pigmentosa reticularis: through the eye of dermoscope - Aditi Bansal; Navneet Kaur; Aminder Singh; Sukhjot Kaur (Wolters Kluwer Medknow Publications, 2023)
Dermatopathia pigmentosa reticularis is a rare ectodermal dysplasia characterized by a triad of generalized reticulate hyperpigmentation, noncicatricial alopecia, and onychodystrophy. We report a case of a 22-year-old male with characteristic features of the diagnostic triad and adermatoglyphia of palm and soles. On dermoscopic examination reticulated hyperpigmented spots, reticulated pigmented spots, monotonous pigmented spots, reticulated hypopigmented spots, with perifollicular hypopigmentation were observed. Dermoscopic findings of palm and soles showed hyperpigmented reticular pattern with dots and adermatoglyphia. Onychoscopy and trichoscopy are also discussed. Histopathology revealed orthokeratosis, epidermal atrophy, increase in melanin pigment in basal layers with vacuolization, and dermal pigmentary incontinence. Other inherited reticulate dermatoses such as Naegeli-Franceschetti-Jadassohn syndrome, dyschromatosis symmetrica hereditaria, and dyskeratosis congenita were considered in differential diagnosis and are discussed.